PENERAPAN ELEMEN PERKEMBANGAN KOGNITIF, PSIKOMOTOR DAN SOSIO-EMOSI DALAM PERMAINAN DALAM MENCAPAI OBJEKTIF KURIKULUM STANDARD PRASEKOLAH KEBANGSAAN - Ismail, Irwan Mahazir; Anis, Siti Khadijah; Subramaniam, Tamil Selvan; Amiruddin, Hasril; Ismail, Mohd Erfy (Online Journal for TVET Practitioners, 2018)
Learning through game in pre-school learning has proven its effectiveness. It is an ideal learning approach to apply for pre-school children. Games is a very important tool teaching effectiveness. Game elements must be considered properly in every activity during the teaching and learning. However, the game elements mus tmeet the requirements of the National Pre-School Standard Curriculum. Based on literature review, developmental elements need to be emphasized in the learning of preschool children. The findings of this literature study emphasize the age and learning objectives that will be achieved through the teaching and learning process based on the elements of development. The implications of these findings will guide the elements that need to be applied in the game in conformity with the National Preschool Standard Curriculum.